Corrections to "A Further Result about 'on the Channel Capacity of Multiantenna Systems with Nakagami Fading'". (10th December 2009) - Lei, Xianfu; Yu, Kai; Fan, Pingzhi
Abstract : We correct some expressions obtained in the above paper. The corrected expressions will be useful for evaluating the channel capacity of wireless communication systems over fading channels.